Effectiveness of a combination of anti-pigmentary products in facial post-inflammatory hyperpigmentation - Nayak, Chitra S.; Ansari, Saba M. M.; Salve, Vrushali; Patil, Shweta (International Journal of Research in Dermatology, 2019)
Background: Post-inflammatory hyperpigmentation (PIH), also has psychosocial implications. Hydroquinone containing preparations though effective, have unacceptable side effects. Molecules like kojic acid, arbutin, vitamins C and E, niacinamide and many others have depigmenting effect, singly or in combination. The objective of this study was to assess the effectiveness and tolerability of a cream containing a combination of niacinamide-4.0%, glycolic acid-2.0%, vitamin E acetate-0.1%, kojic acid dipalmitate-2.0%, soy isoflavones-0.5%, arbutin-2.0%, pterowhite-0.12%, licorice-40% CA-0.12%, ascorbyl glucoside-0.1% (Melaglow-Rich, Abbott Healthcare Pvt. Ltd.) in treatment of PIH. The specific objectives were to evaluate the changes in pigmentation, safety of the cream and patient opinion regarding the cream after 90 days of use. Methods: After IEC approval, adult males and non-pregnant, non-lactating females aged upto 50 years with PIH were included. Those with endocrinopathies who received systemic steroid therapy in the preceding month were excluded. 114 participants who were enrolled in this open-label, non-comparative study, applied study medication (b.i.d) and sunscreen (SPF-30; q.d). Effectiveness was assessed by PIH severity scale, Mexameter assessment, Patients’ and Physicians’ Global Assessment Scale and clinical photographs. Adverse events were documented. Results: Mean PIH score and mean mexameter reading for melanin and erythema in the hyperpigmented and non-hyperpigmented skin reduced by day 90 (p=0.0009, p<0.0001, p<0.001). Significant reduction in physicians’ (p=0.004) and patients’ (p=0.006) global assessment score was evident by day 90. Itching (n=1), burning (n=3) and stinging (n=3) were noted. Conclusions: Melaglow rich cream was found to be effective and well-tolerated in the treatment of PIH.